The Rise of Inhibin A Serum Level in Preterm Labor - Haribudiman, Oky (Indonesian Journal of Obstetrics and Gynecology, 2011)
Objective: The purpose of this study was to measure inhibin A serum level in women with preterm delivery, thus determining any correlation between inhibin A serum and gestational age in preterm delivery. Method: The design of our study was cross sectional with 36 subjects who came to Dr. Hasan Sadikin Hospital, Bandung and six satellite hospitals in July-August 2011 and met inclusion-exclusion criteria. Inhibin A serum level was measured with ELISA. Inhibin A serum level in preterm labor and was compared using independent t test, and correlation between inhibin A serum level and gestational age in patients with preterm labor was calculated using Pearson correlation test. Result: Characteristics test in both groups showed that both are homogeneous and comparable. The mean inhibin A serum level in preterm labor was higher (845.733 pg/ml) compared with preterm gestation (568.203 pg/ml) (p = 0.025). There was a significant correlation between inhibin A serum level and gestational age in preterm labor (p = 0.023) with a correlation coefficient of 0.38, indicating a moderate positive relationship. Conclusion: Inhibin A serum level in preterm labor was higher than preterm pregnancy. In preterm labor, inhibin A serum level increases with gestational age. [Indones J Obstet Gynecol 2011; 35-3: 110-4] Keywords: preterm delivery, inhibin A serum level